Capacity of short circular CFST columns with inner vertical plates welded intermittently. (February 2020) - Thomas, Job; Sandeep, T.N.
Abstract: This paper deals with the strength and deformation characteristics of short circular Concrete-filled Steel Tube (CFST) stiffened columns. The intermittently welded vertical stiffener plates are used to strengthen the steel tubes. Plates are attached to the inner surface of the tube by welding it from outside through the predrilled holes in the tube. The stiffener plates improve the bonding between the steel tube and the concrete and also enhance the confinement in the concrete. The variables of the experimental study are spacing of the weld between the stiffener plate and the circular tube and number of vertical stiffener plates. The weld spacing of 10 t, 15 t, 25 t, 35 t and 50 t, where t is the tube thickness and 3, 4 and 5 numbers of vertical stiffener plates are used in this study. The number of specimens cast and tested in this study is 29. The test results indicate that the strength and deformation of the circular CFST column are significantly influenced by the intermittently welded stiffener plates. The ultimate axial load-carrying capacity of the CFST columns is found to increase by 26% when the spacing of weld is reduced to 10 t from 50 t . A strength prediction model is developed for the CFST columns which are intermittently welded stiffeners. The prediction is found to be in good conformity with the corresponding test data. Highlights: The structural strength and deformation characteristics of stiffened CFST column are studied. The influence of providing the intermittently welded vertical stiffeners is demonstrated. The number of stiffeners and the weld spacing is found to influence the strength of CFST columns. The modified confinement factor for the strength of core concrete is proposed. The model accounting for the weld parameters is proposed for the prediction of axial load-carrying capacity.